Structure–metabolism-relationships in the microsomal clearance of piperazin-1-ylpyridazines. Issue 7 (4th July 2017) - Llona-Minguez, Sabin; Ghassemian, Artin; Baranczewski, Pawel; Desroses, Matthieu; Koolmeister, Tobias; Artursson, Per; Scobie, Martin; Helleday, Thomas
Abstract : In this study, we provide insight into the metabolic profile of a series of piperazin-1-ylpyridazines suffering from rapid in vitro intrinsic clearance in a metabolic stability assay using liver microsomes. Abstract : In this study, we provide insight into the metabolic profile of a series of piperazin-1-ylpyridazines suffering from rapid in vitro intrinsic clearance in a metabolic stability assay using liver microsomes ( e.g. compound1 MLM/HLM t 1/2 = 2/3 min). Aided by empirical metabolite identification and computational predictive models, we designed the structural modifications required to improve in vitro intrinsic clearance by more than 50-fold ( e.g. compound29 MLM/HLM t 1/2 = 113/105 min).